You Are Your Best intervention: Utilizing Person-of-the-Therapist Training in Financial Therapy - Megan A McCoy; Stephen Molchan; Kristy L Archuleta; Ingrid Ponciano (Journal of Financial Therapy, 2023)
The field of financial therapy recognizes the importance of the therapist's self in facilitating effective client outcomes. Self-exploration involves a comprehensive exploration of the therapist's relationship with money, allowing them to leverage their experiences, financial flashpoints, and money scripts ethically and effectively. By engaging in self-exploration, financial therapists become role models for their clients, inspiring them to embark on their personal growth journeys. However, therapists must exercise caution to avoid projecting their beliefs onto clients. This paper explores how one specific program on the self-of-the-therapist exploration, the person-of-the-therapist model (POTT; Aponte, 1982), can be applied to financial therapy self-work. This approach to self-exploration highlights the significance of self-knowledge, awareness, and management in facilitating effective financial therapy. It emphasizes discovering one’s signature theme (patterns, thoughts, or emotions that create challenges in functioning) and their role in shaping therapists' client interactions. Additionally, the use of one’s own and their client’s genogram can facilitate insights. This article introduces a hypothetical case illustration to demonstrate POTT’s application to financial therapy. By embracing the POTT framework, financial therapists can enhance their self-awareness, manage their personal experiences, and optimize their therapeutic effectiveness, thus contributing to clients' financial well-being and personal growth potential.
Keywords: financial therapy; the person-of-the-therapist; self-exploration; signature themes; genograms